Antiproliferative activity of copper(II) glutamine complexes with N,N-donor ligands: Synthesis, characterization, potentiometric studies and DNA/BSA interactions - Kiraz, Sirem; Inci, Duygu; Aydin, Rahmiye; Vatan, Ozgur; Zorlu, Yunus; Cavas, Tolga (Elsevier Science Bv, 2019)
New water soluble copper(II) complexes, - [Cu(phen)(gln)(H2O)]NO3 center dot H2O (1) and [Cu(dmphen)(gln)(H2O)]ClO4 (2) - (phen: 1,10-phenanthroline, dmphen: 4,7-dimethyl-1,10-phenanthroline, gln: L-glutamine), have been synthesized and characterized by CHN analysis, ATR-FT-MIR, ESI-MS and single-crystal X-ray diffraction techniques. Binary and ternary complexes of copper(II) with the selected ligands have been investigated using potentiometric methods in 0.1 M KCl aqueous ionic media at 298.2 K. The protonation constants of the selected ligands and the stability constants of the complexes 1 and 2 have been calculated from the potentiometric data using the BEST software package and the potentiometric results have been analyzed using the SPE software package. The binding interaction of the complexes with calf thymus DNA (CT-DNA) was investigated by electronic absorption and emission spectroscopic methods revealed that the complexes could interact with CT-DNA via a moderate intercalation mode. The fluorescence quenching mechanism of bovine serum albumin (BSA) by the complexes was analyzed and the binding constant has been calculated. In vitro antiproliferative effect of the complexes was examined on human tumor cell lines (Caco-2, A549 and MCF-7) and healthy cells (BEAS-2B). The complex 2 showed remarkable antiproliferative activity compared to the complex 1 and cisplatin. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Copper(II) complexes; 1,10-Phenanthroline; 4,7-Dimethyl-1,10-phenanthroline; Glutamine; DNA/BSA interactions; Antiproliferative activity